2019
DOI: 10.1149/2.0031909jes
|View full text |Cite
|
Sign up to set email alerts
|

Perspective—Micro Photosynthetic Power Cells

Abstract: Micro-photosynthetic power cell (μPSC) is one of the emerging energy harvesting technologies which harvests energy using light (photosynthesis) and carbohydrate metabolism in dark (respiration) for low-power (mW range) applications. μPSC is a green technology that not only uses solar power and algae, but also provides power in both dark and light conditions. This perspective article provides state of the art of μPSC technology in terms of fabrication, mathematical modeling and energy harvesting circuit design.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 64 publications
0
35
0
Order By: Relevance
“…Theoretically, OCV should be the Nernst reversible voltage, however, because of various losses, such as ohmic losses, concentration losses, and activation losses, the OCV is lesser. For more details on the OCV, readers are directed to References [10,13]. In Reference [3] OCV was 330 mV after 4 min of the operating time, and when it was subjected to a direct light intensity of 2000 µmole photons m −2 s −1 , OCV sharply increased to 470 mV and stabilized within a short period of 2 min.…”
Section: Performance Parameters Of the Micro-photosynthetic Power Celmentioning
confidence: 99%
See 3 more Smart Citations
“…Theoretically, OCV should be the Nernst reversible voltage, however, because of various losses, such as ohmic losses, concentration losses, and activation losses, the OCV is lesser. For more details on the OCV, readers are directed to References [10,13]. In Reference [3] OCV was 330 mV after 4 min of the operating time, and when it was subjected to a direct light intensity of 2000 µmole photons m −2 s −1 , OCV sharply increased to 470 mV and stabilized within a short period of 2 min.…”
Section: Performance Parameters Of the Micro-photosynthetic Power Celmentioning
confidence: 99%
“…The high cost is due to use of noble materials as electrodes/current collectors and the proton exchange membrane Nafion. A recent work by Tanneru et al [10] provides a detailed possibilities for performance enhancement and cost reduction.…”
Section: Avenues For Cost Reduction Of the Micro-photosynthetic Powermentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, nano-composite catalyst showed promising results: Kodali et al 7 enhanced the MFC performance by using an iron-graphence catalyst and Karthikeyan et al 8 reported 3D flower-like FeWO 4 /CeO 2 on rGO produced high power and stable power output from alga BPV devices. BPV devices have been reported to generate current and power densities, respectively, in the range of 0.17 to 993 mA m −2 and up to 400 mW m −2 with various BPV reactors and operating parameters 1 . The maximum power density reported thus far was generated from a two-chamber device using an algae suspension, mediated electron transfer, and a gold-inscribed Nafion membrane 9 .…”
mentioning
confidence: 99%